PENGARUH HARGA DAN PROMOSI TERHADAP MINAT BELI SMARTPHONE SAMSUNG DI SAMSUNG STORE PLASA MARINA SURABAYA - Visca, Aulia; Lia, Nirawati (Jurnal Bisnis Indonesia, 2021)
Smartphone is a mobile phone that has features or high-level capabilities that are often in use like a computer. The presence of a smartphone can provide various benefits for its usersso that the public demand for smartphones is increasing and increasing. The purpose of thisstudy was to examine and analyze the effect of price variables (X1) and product variables (X2)on Samsung smartphone purchase interest variables (Y). This type of research uses descriptivequantitative approach. The population in this study is consumers who are interested and buySamsung smartphones at Samsung Store Plaza Marina Surabaya. The number of samplesdetermined was 100 respondents, the sampling method used was non-probability sampling bydetermining the sample using a purposive sampling technique. Data collection methodsthrough questionnaires. The data analysis tool uses multiple linear regression, with processingtools IBM SPSS Statistics 25. From the results of the study note that the price variable (X1) and promotion (X2)simultaneously have a significant effect on the purchase interest variable (Y) can be seen thatthe F-count (17,874)> F-table (3.09). Besides the price variable (X1) and promotion (X2) thereis also a partially significant influence on buying interest (Y). It can be seen that the pricevariable with a calculated value (4,405)> t table (1,985) and a promotional variable with acalculated value (t) 2,857)> t table (1,985). Keywords: Smartphone, Price, Promotion, Purchase Interest  DOI : https://doi.org/10.33005/jbi.v12i1.2604